Performance comparison of nitrile rubber 4105 with high-bound acrylonitrile content and similar products - "HU Hai-hua, WU Yu, XU Dian-hong, ZHAO Hong-guo, HUANG Xi-dai, HE Lian-cheng, GONG Zi-qing, ZHOU Lei" (Hecheng xiangjiao gongye)
Microstructures, molecular weights and their distributions of domestic nitrile rubber (NBR) products with high bound acrylonitrile content NBR 4105, NBR 3604 and NBR 4155 and imported pro-ducts N 220 S raw rubber, curing characteristics and processabilities of compounds, physical and mechanical properties, abrasion resistance, and thermal-oxidative aging resistance of vulcanizates were compared, and the application of four kinds of NBR and NBR 3604/NBR 4105 blend in oilfield drilling pump valve rubber were also explored. The results showed that weight-average molecular weight and number-average molecular weight of NBR 4105 were slightly lower than those of the other three kinds of NBR, molecular weight distribution of NBR 4105 was slightly narrower and comparable to that of N 220 S, and bound acrylonitrile content of NBR 4105 was the highest. NBR 3604 had the lowest trans-1,4-unit content and the highest cis-1,4-unit content. Scorch time of the four kinds of NBR were basically the same, NBR 3604 had the slowest vulcanization rate, the processabilities of NBR 3604 and NBR 4105 were slightly worse than those of N 220 S and NBR 4155 with of NBR 3604 having the worst processability. Tensile strength and modulus at 300% of NBR 3604 vulcanizate were slightly higher, it had smaller abrasion resistance and the smallest compression permanent set, and NBR 4105 vulca-nizate had the best thermal-oxidative aging resistance. NBR 3604/NBR 4105 blend was suitable for the manufacture of oilfield drilling pump valve rubber with better comprehensive performance. was.